Fresno County Bar Association Annual Bar Banquet at TorNino's - Watkins, Howard::::::::: (1988)
Justice James Ardaiz, Judge Dennis Beck, Justice Nicholas Dibiaso, Judge Gary Austin, and Justice Hollis Best